2021
DOI: 10.4028/www.scientific.net/kem.872.1
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Impact Resistance of Concrete Containing Steel Fibers

Abstract: This study is an experimental study aims to examine the effect of utilization of straight, and low cost steel fibers on the impact resistance of concrete. The impact resistance of steel fiber reinforced concrete (SFRC) was assessed using drop weight test as per ACI committee 544. The steel fibers were randomly dispersed in concrete during mixing. Five mixes made with steel fibers dosages of 0% (control mix), 0.5%, 1%, 1.25% and 1.5% by volume of concrete were examined in the study. The results show that mixes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…It is also concluded that incorporating waste materials into pervious concrete would significantly reduce the impact of concrete on the environmental and enhances the sustainability of concrete [9]. Furthermore, it has been experimentally found, using drop weight test, that adding steel fibers to the concrete mixes with 1.25% by volume of concrete improves the impact resistance of concrete compared to that of plain concrete [10].…”
Section: Introductionmentioning
confidence: 99%
“…It is also concluded that incorporating waste materials into pervious concrete would significantly reduce the impact of concrete on the environmental and enhances the sustainability of concrete [9]. Furthermore, it has been experimentally found, using drop weight test, that adding steel fibers to the concrete mixes with 1.25% by volume of concrete improves the impact resistance of concrete compared to that of plain concrete [10].…”
Section: Introductionmentioning
confidence: 99%